Establishment and application of Agrobacterium-delivered CRISPR/Cas9 system for wild tobacco (Nicotiana alata) genome editing - Yuan, Cheng; Zeng, Jianmin; Liu, Yong; Yu, Haiqin; Tong, Zhijun; Zhang, Jianduo; Gao, Qian; Wang, Zhong; Sui, Xueyi; Xiao, Bingguang; Huang, Changjun (Frontiers in Plant Science, 2024)
Clustered regularly interspaced short palindromic repeats (CRISPR)-associated protein 9 (CRISPR-Cas9) system has been widely applied in cultivated crops, but limited in their wild relatives. Nicotiana alata is a typical wild species of genus Nicotiana that is globally distributed as a horticultural plant and well-studied as a self-incompatibility model. It also has valuable genes for disease resistance and ornamental traits. However, it lacks an efficient genetic transformation and genome editing system, which hampers its gene function and breeding research. In this study, we developed an optimized hypocotyl-mediated transformation method for CRISPR-Cas9 delivery. The genetic transformation efficiency was significantly improved from approximately 1% to over 80%. We also applied the CRISPR-Cas9 system to target the phytoene desaturase (NalaPDS) gene in N. alata and obtained edited plants with PDS mutations with over 50% editing efficiency. To generate self-compatible N. alata lines, a polycistronic tRNA-gRNA (PTG) strategy was used to target exonic regions of allelic S-RNase genes and generate targeted knockouts simultaneously. We demonstrated that our system is feasible, stable, and high-efficiency for N. alata genome editing. Our study provides a powerful tool for basic research and genetic improvement of N. alata and an example for other wild tobacco species.